Automatic detection and recognition of traffic signs - Hossain, M. Sajjad; Hasan, M. Mahmudul; Ameer Ali, M.; Kabir, Md. Humayun; Shawkat Ali, A B M (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
Automatic detection of road sign is a challenging but demanding job. A new approach namely automatic detection and recognition of traffic signs (ADRTS) considering color segmentation, moment invariants, and neural networks has been proposed in this paper. Experimental result proves the superior performance in the detection and recognition of road signs. Computational time complexity is also quite low that makes it applicable for the real time system.